2020
DOI: 10.1186/s11556-020-00244-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a four week detraining period on physical, metabolic, and inflammatory profiles of elderly women who regularly participate in a program of strength training

Abstract: Background: Human aging has innumerable health implications, including loss of muscle mass and increased circulating inflammatory markers. Resistance exercise in the elderly can prevent muscle mass loss and improve the inflammatory profile. Conversely, detraining can reverse this picture. Thus, there is a strong need for studies with the elderly population to clarify the real impacts of a training interruption. Therefore, the objective of this study was to analyze the inflammatory profile of resistance trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 59 publications
0
1
0
1
Order By: Relevance
“…Within this frame, several authors have reported significant reductions in the performance of all functional fitness components even after a relatively short detraining period (i.e., lasting at least 4/6 weeks) [ 54 , 55 , 56 ]. Since the evaluation of both physical and biomechanical parameters was not assessed after the training interruption (i.e., before starting the intervention program), we cannot rule out that the detraining period may negatively impact these variables, resulting in a significant decrease in physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Within this frame, several authors have reported significant reductions in the performance of all functional fitness components even after a relatively short detraining period (i.e., lasting at least 4/6 weeks) [ 54 , 55 , 56 ]. Since the evaluation of both physical and biomechanical parameters was not assessed after the training interruption (i.e., before starting the intervention program), we cannot rule out that the detraining period may negatively impact these variables, resulting in a significant decrease in physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Quando o total de passos diários reduz de 10.000 para 1.500 passos, em apenas 14 dias há um aumento signifi cativo da AC e CA, o que contribui tanto com o risco de desenvolvimento de DCNT como da aproximação dos componentes e comorbidades da SM 27 . Nessa mesma linha, um estudo recente demonstrou que mesmo curto período de destreinamento é capaz de promover RI e aumento nos níveis de LDL em idosas treinadas 28 . Portanto, tais evidências mostram que ao mesmo tempo que o aumento do NAF é importante para prevenção e controle de SM, reduções signifi cativas do NAF aumentam a probabilidade de desenvolvimento de DCNT, inclusive SM 29 .…”
Section: Relação Entre O Nível De Atividade Física E a Progressão Dos...unclassified